2017
DOI: 10.1111/ecc.12723
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of irinotecan/platinum versus etoposide/platinum chemotherapy for extensive-stage small cell lung cancer: A meta-analysis

Abstract: This meta-analysis was performed to compare the effects and toxicities between irinotecan/platinum (IP) and etoposide/platinum (EP) regimens as the fist-line treatment of patients with extensive-stage small cell lung cancer (E-SCLC). A systematic search was made of MEDLINE, Cochrane, ISI Web of Science and SCOPUS databases. Randomised clinical trials on treatment of E-SCLC with the IP regimens, compared with EP regimens, were reviewed. Studies were pooled to hazard ratio (HR), relative risk (RR) and odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…[4] However, discrepancies exist in the comparative efficacy of these treatments: recent meta-analyses of randomized controlled trial (RCT) data have shown that platinum chemotherapy in combination with irinotecan increases overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and 1-year survival in ED-SCLC, compared to platinum/etoposide regimens. [8, 9] In contrast, a similar meta-analysis did not report any ORR or disease control rate improvements with the same regimen, providing little conclusive data on the clear superiority of one treatment over the others. [10] Despite these results, the survival benefit reported in RCTs remains modest regardless of the treatment type used.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, discrepancies exist in the comparative efficacy of these treatments: recent meta-analyses of randomized controlled trial (RCT) data have shown that platinum chemotherapy in combination with irinotecan increases overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and 1-year survival in ED-SCLC, compared to platinum/etoposide regimens. [8, 9] In contrast, a similar meta-analysis did not report any ORR or disease control rate improvements with the same regimen, providing little conclusive data on the clear superiority of one treatment over the others. [10] Despite these results, the survival benefit reported in RCTs remains modest regardless of the treatment type used.…”
Section: Introductionmentioning
confidence: 99%
“…Irinotecan, a topoisomerase 1 inhibitor, is a chemotherapeutic agent widely used for the treatment of a variety of cancers, including small cell lung cancer, gastrointestinal cancer, and breast cancer [ 8 11 ]. However, the role of irinotecan in the tumor–immunity cycle has not yet been investigated and there are few clinical studies evaluating the combination of irinotecan with PD-L1/PD-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“… 2 6 Other groups argued that relying on significance based on p value alone was not scientific, 22 , 23 and preferred to accept “the trend” and the result from meta-analyses. 11 13 Schmittel et al claimed that the CBDCA+ETP regimen remained the standard treatment because the CBDCA+CPT11 regimen could not demonstrate statistically significant superiority in OS of patients with ED-SCLC (HR 1.29, 95% CI 0.96–1.73, p = 0.095; median OS 10.0 month versus 9.0 months, p = 0.06). 24 Although the pooled HRos calculated using data from Hermes and Schmittel was 0.72 (95% CI 0.59–0.90, p = 0.002) without heterogeneity (P for heterogeneity = 0.2, I 2 = 0%) at the time of the publication of the study Schmittel ( Figure 4B ), 11– 13 , 24 , 25 several groups agreed with the results of the Schmittel and continued to use CBDCA+ETP as the standard reference treatment ( Table 1 , Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%